PENGEMBANGAN SOFT SKILL DAN HARD SKILL DI ERA DIGITAL: SEBUAH TINJAUAN SISTEMATIS - Setyako, Stevani Dewi; Rahma, Sitta; Rizal, Yul; Veranita, Mira (ABISATYA DINAMIKA ISWARA, 2024)
Background: The rapid development of digital technology has intensified the need for mastering both soft and hard skills to improve individual competitiveness in today’s workforce. Both skill sets play a critical role in determining individual performance and job readiness. Objective: This study aims to systematically review the impact of soft skill and hard skill development on performance in the digital era. Methods: A systematic review was conducted using relevant keywords to search online scientific databases for articles published between 2020 and 2025. After applying inclusion and exclusion criteria, 9 studies were selected from an initial pool of 129 publications. Results: The analysis revealed that the development of soft skills such as self-awareness, empathy, and relationship management, along with hard skills such as technical proficiency, significantly influences employee performance, student job readiness, and the formation of self-efficacy. Conclusion: A balanced development of both soft and hard skills is essential for individual success in both academic and professional settings. In the digital era, these competencies are vital for adaptability and continuous learning. Suggestion: Integration into educational curriculum, collaboration between academia and industry, enhancing hr roles in the workplace, development of interactive digital modules. Keywords: soft skill, hard skill, performance, digital era